Sosialisasi Penerapan 5R pada Pekerja Bengkel Reparasi Truk di CV. Karya Cipta Baru - Febrianti, Diah Rini; Ratriwardhani, Ratna Ayu; Azzahra, Aanisah; Erwin Kusuma, Muhammad; Sahri, Moch (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The progress of the industrial world demands work to be done more easily, quickly and efficiently. One principle that must be built to achieve this goal is to instill a work culture. The work culture that is widely applied in the world is 5R (Concise, Neat, Clean, Caring and Diligent). The 5R work culture/system is very necessary to avoid irregular placement of tools and other facilities in the workplace, especially industry. This community service is intended to provide insight, strengthen knowledge and skills in implementing 5R for leaders and employees, especially at CV. New Creation. The method used in socialization activities at CV. This New Creation work is by means of interviews, surveys and outreach. The target for this socialization activity is 10 workers. The poster presented was themed "Cultivate 5R in the Workplace". The author also provides pre-tests and post-tests related to OSH culture and the application of 5R to workers with the aim of measuring the level of knowledge of workers. The results of the evaluation showed that of the 10 employees who participated in the socialization, the level of knowledge and understanding of employees towards the 5R program increased.